Testis development in the Japanese eel is affected by photic signals through melatonin secretion - Ji-Yeon Hyeon; Jun-Hwan Byun; Eun-Su Kim; Yoon-Seong Heo; Kodai Fukunaga; Shin-Kwon Kim; Satoshi Imamura; Se-Jae Kim; Akihiro Takemura; Sung-Pyo Hur (PeerJ, 2021)
Objective According to reported spawning characteristics of Japanese eel, Anguilla japonica, which exhibit spawning and migration patterns that are synchronized with lunar cycles and photoperiod, we hypothesized that a close association exists between specific photic signals (daylight, daylength, and moonlight) and endocrinological regulation. Given the photic control in melatonin secretion, this hypothesis was tested by investigating whether melatonin signals act as mediators relaying photic signals during testis development in the eel. Methods We examined changes in melatonin-secretion patterns using time-resolved fluorescence immunoassays in sexually immature and mature male Japanese eels under the condition of a new moon (NM) and a full moon (FM). Results The eye and plasma melatonin levels exhibited a nocturnal pattern under a 12-h light: dark cycle (12L12D) or under constant darkness (DD), but not with constant light (LL). Eye melatonin levels were similar under the 12L12D and short-day (9L15D) conditions. In the long-day condition (15L9D), secreted plasma melatonin levels were stable, whereas short-day melatonin secretion began when darkness commenced. Sexual maturation began at 8 weeks following intraperitoneal injection of human chorionic gonadotropin (hCG), and NM exposure led to significantly higher eye and plasma melatonin levels compared with those detected under FM exposure.